Emotional regulation and clinical symptomatology when experiencing the illness of a close person - Fernandes, Isabel (2019)
3rd International Congress of CiiEM - Research and Innovation in Human and Health Sciences. Monte da Caparica, Portugal, 20-22 June 2018